Catabolite-resistant sporulation (crsA) mutations in the Bacillus subtilis RNA polymerase sigma 43 gene (rpoD) can suppress and be suppressed by mutations in spo0 genes. - Kawamura, F (1985)
The catabolite-resistant sporulation (crsA) mutation is able to overcome the repressive effect of glucose on sporulation in Bacillus subtilis. Three chromosomal crsA mutations, crsA1, crsA4, and crsA47, were transferred by the "gene conversion" process to B. subtilis plasmid pRPD11, which consists of the entire wild-type rpoD coding sequence, encoding the major sigma 43 factor of B. subtilis RNA polymerase, and pUB110. By DNA sequence analysis we showed that all three crsA mutations were identical two-base changes, CCT (proline) to TTT (phenylalanine), within the rpoD coding sequence. Furthermore, the crsA47 mutation restored spo0J and spo0K sporulation to wild-type levels and partially improved the sporulation efficiencies of spo0B, spo0D, and spo0F. Extragenic suppressors (scr) of crsA47 included mutations in spo0A, spo0D, spo0F, and spo0K plus other mutations that have not been specifically identified. Thus sigma 43 appears to be involved in catabolite repression by glucose, to interact either directly or indirectly with spo0 gene products, and to play an important role in the initiation of spore development in B. subtilis.